Air velocity influences thermoregulation and endurance exercise capacity in the heat - Otani, H.; Kaya, M.; Tamaki, A.; Watson, P.; Maughan, R. J. (Applied Physiology, Nutrition, and Metabolism, 2018)
This study examined the effects of variations in air velocity on time to exhaustion and thermoregulatory and perceptual responses to exercise in a hot environment. Eight male volunteers completed stationary cycle exercise trials at 70% peak oxygen uptake until exhaustion in an environmental chamber maintained at 30 °C and 50% relative humidity. Four air velocity conditions, 30, 20, 10, and 0 km/h, were tested, and the headwind was directed at the frontal aspect of the subject by 2 industrial fans, with blade diameters of 1 m and 0.5 m, set in series and positioned 3 m from the subject`s chest. Mean ± SD time to exhaustion was 90 ± 17, 73 ± 16, 58 ± 13, and 41 ± 10 min in 30-, 20-, 10-, and 0-km/h trials, respectively, and was different between all trials (P < 0.05). There were progressive elevations in the rate of core temperature rise, mean skin temperature, and perceived thermal sensation as airflow decreases (P < 0.05). Core temperature, heart rate, cutaneous vascular conductance, and perceived exertion were higher and evaporative heat loss was lower without airflow than at any given airflow (P < 0.05). Dry heat loss and plasma volume were similar between trials (P > 0.05). The present study demonstrated a progressive reduction in time to exhaustion as air velocity decreases. This response is associated with a faster rate of core temperature rise and a higher skin temperature and perceived thermal stress with decreasing airflow. Moreover, airflow greater than 10 km/h (2.8 m/s) might contribute to enhancing endurance exercise capacity and reducing thermoregulatory, cardiovascular, and perceptual strain during exercise in a hot environment.